Enhanced adherence of mouse fibroblast and vascular cells to plasma modified polyethylene - Reznickova, Alena; Novotna, Zdenka; Kolska, Zdenka; Kasalkova, Nikola Slepickova; Rimpelova, Silvie; Svorcik, Vaclav (Materials science & engineering. C, Materials for biological applications, 2015)
Since the last decade, tissue engineering has shown a sensational promise in providing more viable alternatives to surgical procedures for harvested tissues, implants and prostheses. Biomedical polymers, such as low-density polyethylene (LDPE), high-density polyethylene (HDPE) and ultra-high molecular weight polyethylene (UHMWPE), were activated by Ar plasma discharge. Degradation of polymer chains was examined by determination of the thickness of ablated layer. The amount of an ablated polymer layer was measured by gravimetry. Contact angle, measured by goniometry, was studied as a function of plasma exposure and post-exposure aging times. Chemical structure of modified polymers was characterized by angle resolved X-ray photoelectron spectroscopy. Surface chemistry and polarity of the samples were investigated by electrokinetic analysis. Changes in surface morphology were followed using atomic force microscopy. Cytocompatibility of plasma activated polyethylene foils was studied using two distinct model cell lines; VSMCs (vascular smooth muscle cells) as a model for vascular graft testing and connective tissue cells L929 (mouse fibroblasts) approved for standardized material cytotoxicity testing. Specifically, the cell number, morphology, and metabolic activity of the adhered and proliferated cells on the polyethylene matrices were studied in vitro. It was found that the plasma treatment caused ablation of the polymers, resulting in dramatic changes in their surface morphology and roughness. ARXPS and electrokinetic measurements revealed oxidation of the polymer surface. It was found that plasma activation has a positive effect on the adhesion and proliferation of VSMCs and L929 cells.
Keywords: Polyethylene (PE); Myocytes, Smooth Muscle; Muscle, Smooth, Vascular; polyethylen; Cell Line; Aging; fibroblasty; Fibroblasts; Cell Proliferation; Metabolic activity; Cell adhesion; Plasma treatment; Polyethylene; buněčná adheze; krysa rodu Rattus; Animals; svaly hladké cévní; zvířata; Rats; myši; krevní plazma; buněčné linie; proliferace buněk; Ablation; Mice; myocyty hladké svaloviny; Plasma; Cell Adhesion